British War Time Control of Aluminum - Backman, Jules; Fishman, Leo (Quarterly Journal of Economics, 1941)
Introduction: characteristics of the industry, 18. — The time-schedule of control, 20. — Organization and administration of control, 22. — Maximum prices: virgin aluminum, 26; aluminum alloy, 27; secondary aluminum, 28; aluminum scrap, 28. — Aluminum and other non-ferrous metal prices, 29. — Maintenance and expansion of supply, 32. — Collection and utilization of scrap, 38. — Appeal to housewives, 39. — Control over demand, 41. — Summary and conclusions, 46.